Climate and gypsum parent material shape biocrust communities and moss ecology in the Chihuahuan and Mojave Deserts - Katelyn G. Gobbie; Nicole Pietrasiak; Brian M. Jusko; Rebecca E. Drenovsky (Geoderma)
Biological soil crust communities (biocrusts) establishing on gypsum soils have been well-documented for their prolific appearance and rich diversity of lichens and bryophytes. However, studies characterizing gypsum biocrusts have occurred primarily outside of the U.S., most of which lack comparisons to other soil types. We conducted intensive field surveys to evaluate the ground cover and frequency of biocrust functional groups and moss species on gypsum and non-gypsum soils in the U.S. regions with the most extensive gypsum outcrops, the northern Chihuahuan and eastern Mojave Deserts. Study sites were stratified by geomorphology and paired, so that every gypsum site was matched with a non-gypsum site in the same region. We employed canonical correspondence analysis (CCA) to relate the observed differences in biocrust abundance and composition across soil types to distinct environmental variables. Additionally, we assessed species richness of biocrust mosses on gypsum versus non-gypsum soils, as well as in the Chihuahuan versus Mojave Deserts. Our results indicate that differences in biocrust communities on gypsum and non-gypsum soils are predominantly due to gypsum’s profuse dark algal (mostly cyanobacteria-formed) rather than lichen and moss biocrusts in these two hot desert biomes. Biocrust functional groups did not exhibit distinct associations with environmental variables. However, moss species appear to be strongly influenced by environmental variables and exhibited differential preferences for substrate parent material. Moss species richness was greater on gypsum soils and, surprisingly, in the hottest and driest North American Desert, the Mojave. Differences in species richness across deserts were strongly correlated to mean annual and seasonal temperatures, as well as mean winter precipitation. Overall, our data suggest that environmental and climate conditions all play important roles in the ecology of biocrusts, specifically moss diversity and distribution, in the northern Chihuahuan and eastern Mojave Deserts of the U.S. More importantly, we emphasize that gypsum soils of the U.S. are unique refugia for moss-forming biocrusts.